Opportunity cost, inattention and the bidder's curse - David Freeman; Erik O. Kimbrough; J. Philipp Reiss (Karlsruher Institut für Technologie (KIT), Institut für Volkswirtschaftslehre (ECON), 2017)
Recent research suggests that auction winners sometimes fall prey to a "bidder's curse", paying more for an item at auction than they would have paid at a posted price. One explanation for this phenomenon is that bidders are inattentive to posted prices. We develop a model in which bidders' inattention, and subsequent overbidding, is driven by a rational response to the opportunity cost of acquiring information about the posted price. We test our model in a laboratory experiment in which subjects bid in an auction while facing an opportunity cost of looking up the posted price. We vary the opportunity cost, and we show that information acquisition decreases and consequently overbidding increases with opportunity cost as predicted.
urn:nbn:de:swb:90-685119
Keywords: C72; C92; D44; 330; Auctions; Bidder's Curse; Limited Attention; Experiments; Rational Ignorance